If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + 13 = 374 Reorder the terms: 13 + g = 374 Solving 13 + g = 374 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + g = 374 + -13 Combine like terms: 13 + -13 = 0 0 + g = 374 + -13 g = 374 + -13 Combine like terms: 374 + -13 = 361 g = 361 Simplifying g = 361
| 2a-1=1 | | w/2-18=53 | | -23x+15=-11x-69 | | 2w^2+10w+28=(w+6)(w+6) | | 4m^3+9mn+4m^2+9n= | | 5z-2(z-6)=2+42 | | 3/8x-4=21 | | 4n-11=3 | | -8-6(-7z-4)=(-3z+3)-6 | | x-7/8=4x+1/2 | | 1/3+5/6(7/4) | | -7x-15=-13x-63 | | -x^2+3x+28=0 | | 2x^2+4x+340=0 | | 1/4(7/6)-1/8 | | -21x+1=-9x-11 | | 3r=r-4(2+r) | | -10+11=3+m | | 5/6-5/9(5/4) | | 6(4x-1)=3(x-7) | | 4x-4=-8x+116 | | 4x/3+25=33 | | 4(a+5)=5+a | | x^2-(4x+581)=144 | | 2/3m+a=a+r | | 29/30(3/2) | | 5.9+x=2.1 | | 1/6+4/5 | | 4s^2+3s=12 | | 3(x+1)=2x-7 | | 4(-6+-3p)+-8+p= | | x-5/9=-2/3 |